Pengaruh Peran Ganda, Lingkungan Kerja, dan Beban Kerja Terhadap Kinerja Tenaga Kesehatan Wanita Melalui Kendali Diri Sebagai Variabel Intervening (Studi pada Tenaga Kesehatan Wanita Di Puskesmas Burneh Bangkalan) - Aziz, Latifatul Hamida; Djaelani, Abdul Kodir; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of dual roles, work environment and workload on performance through self-control as an intervening variable in female health workers at the Burneh Bangkalan Community Health Center. This research uses quantitative methods with Path Analysis techniques. The respondents for this research were 45 respondents at the Burneh Bangkalan. Data were analyzed using SPSS (Statistical Program for Social Science). The results of this research show that: (1) Dual roles have a significant positive effect on the performance of female health workers, (2) The work environment has a positive and significant effect on the performance of female health workers, (3) Workload has a significant positive effect on the performance of female health workers, ( 4) Dual roles have an insignificant negative effect on self-control of female health workers, (5) Work environment has an insignificant negative effect on self-control, (6) Workload has a significant negative effect on self-control, (7) self-control has an insignificant positive effect on self-control. performance. (8) Significant positive indirect influence of dual roles on performance through self-control, (9) Significant positive indirect influence of work environment on performance through self-control, (10) Significant positive indirect influence of workload on performance through self-control. Keywords: Dual Role, Work Environment, Workload, Performance, Self-Control